South American missionaries' records, 1844-1919. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2009)
Includes most of the material held in the SAMS archives for the period up to 1919. When originally founded in 1844, this Church of England-affiliated organisation was called the Patagonian Mission. This collection reproduces the minute books, reports from the mission field, articles and photographs on the geography, anthropology, natural history and economic development for the society's magazine, launched in 1867, as well as the journals of its Anglican founder, Captain Allen Gardiner, and two others of its missionaries, Edward Bernau and Adolfo Henriksen.
Date range: 1844-1919.
Keywords: Missionaries -- South America -- History -- 19th century; Missionaries -- South America -- History -- 20th century; Patagonian Missionary Society; Missions -- South America -- History -- 19th century; Missions -- South America -- History -- 20th century